2008
DOI: 10.1142/s021773230802700x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically Induced Scalar Quark Confinement

Abstract: We employ a functional approach to investigate the confinement problem in quenched Landau gauge QCD. We demonstrate analytically that a linear rising potential between massive quarks is generated by infrared singularities in the dressed quark-gluon vertex. The selfconsistent mechanism that generates these singularities is driven by the scalar Dirac amplitudes of the full vertex and the quark propagator. These can only be present when chiral symmetry is broken. We have thus uncovered a novel mechanism that dire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
224
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(239 citation statements)
references
References 25 publications
15
224
0
Order By: Relevance
“…Some of the most representative works in this direction include: (i) Focusing only on the form factors of the tensors appearing in the tree-level vertex [first equation in (A2)], and using a power-counting scheme, the authors of [100] found that the infrared limit of the "symmetric configuration" (q 2 = r 2 = p 2 ) shows a divergent power-law behavior of the type (p 2 ) −3κ , where κ = 0.59 is the typical parameter of the so-called "scaling solutions".…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most representative works in this direction include: (i) Focusing only on the form factors of the tensors appearing in the tree-level vertex [first equation in (A2)], and using a power-counting scheme, the authors of [100] found that the infrared limit of the "symmetric configuration" (q 2 = r 2 = p 2 ) shows a divergent power-law behavior of the type (p 2 ) −3κ , where κ = 0.59 is the typical parameter of the so-called "scaling solutions".…”
Section: Discussionmentioning
confidence: 99%
“…This structure is certainly useful beyond the present investigation, for example if devising truncation schemes. Implicitly this was already used for enhancing the respective reliability: the coinciding results for the infrared asymptotics from DSE [8,9,10,12] and FRG [11,23,25] are non-trivial as the functional equations are sufficiently different.…”
Section: Discussionmentioning
confidence: 99%
“…In [12] the self-consistency of (64) for the whole tower of vertex DSEs has been shown. The dominance of ghost loops in the tower of DSEs is equivalent to the dominance of the Faddeev-Popov determinant over the Yang-Mills action, as proposed in [22].…”
Section: Uniqueness Of Infrared Asymptoticsmentioning
confidence: 94%
See 1 more Smart Citation
“…The investigation of the infrared behavior of the ghost and gluon n-point functions of Refs. [17,18] The solutions of the gap equation (7) for the quark propagator amplitudes A(s) and B(s)…”
Section: Effect Of 3-point Gluon Function Dressingmentioning
confidence: 99%